Depletion of microglia augments the dopaminergic neurotoxicity of MPTP. Issue 6 (22nd January 2018) - Yang, Xiaoxia; Ren, Honglei; Wood, Kristofer; Li, Minshu; Qiu, Shenfeng; Shi, Fu-Dong; Ma, Cungen; Liu, Qiang
ABSTRACT: The activation of microglia and the various substances they produce have been linked to the pathologic development of Parkinson's disease (PD), but the precise role of microglia in PD remains to be defined. The survival of microglia depends on colony‐stimulating factor 1 receptor (CSF1R) signaling, and CSF1R inhibition results in rapid elimination of microglia in the central nervous system. Using a mouse PD model induced by 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP) treatment, we showed that the depletion of microglia via the CSF1R inhibitor PLX3397 exacerbated the impairment of locomotor activities and the loss of dopaminergic neurons. Further, depletion of microglia augmented the production of inflammatory mediators and infiltration of leukocytes in the brain after MPTP exposure. Microglia depletion‐induced aggravation of MPTP neurotoxicity was also seen in lymphocyte‐deficient mice. In addition, the depletion of microglia did not affect the production of brain‐derived neurotrophic factor, but it dramatically augmented the production of inflammatory mediators by astrocytes after MPTP treatment. Our findings suggest microglia play a protective role against MPTP‐induced neuroinflammation and dopaminergic neurotoxicity.—Yang, X., Ren, H., Wood, K., Li, M., Qiu, S., Shi, F.‐D., Ma, C., Liu, Q. Depletion of microglia augments the dopaminergic neurotoxicity of MPTP. FASEB J. 32, 3336–3345 (2018). www.fasebj.org